500 The Four Year Clinical and Economic Impact of an Extended Screening Program for Developmental Dysplasia of the Hip in Cardiff and Vale University Health Board. (12th October 2021) - Poacher, A; Froud, J; Marsh, L; Carpenter, C
Abstract: Aim: Early detection of DDH is associated with the increased success of non-surgical treatment. Therefore, Cardiff and Vale Health Board (CAVUHB) implemented an extended screening program for Developmental dysplasia of the Hip (DDH) to improve neonatal public health within the population. Method: A 4-year prospective case-control study of all patients born between 01/01/2016-31/12/2019 (n = 21843) who underwent ultrasonographic screening for DDH in CAVUHB. Ultrasounds were graded using Graf's classification, with treatment outcomes determined by patient's records and costings based on NHS tariffs. Results: Screening of those with risk factors diagnosed 49% of treated DDH cases. Screening for risk factors cost CAVUHB £175, 000 per annum, with a cost per favourable outcome of £12351. The mean cost of DDH treatment of a late presenting patient was £23, 782, incurring a cost reduction of 48%. Cost-effectiveness and positive predictive value (PPV) of calcaneovalgus malformations, oligohydramnios, and plagiocephaly demonstrating PPV similar to that of primary risk factors. Calcaneovalgus malformations demonstrated significantly higher PPV than primary risk factors for DDH (p < 0.05). Conclusions: CAVUHB cost-effectively reduced morbidity and surgical mortality within the neonatal population, as a result of its extended screening program for DDH. The novel findings of prevalence and predictive value of secondary risk factors as a marker of treatable DDH are significant, as currently they are not included in the national new-born and infant physical examination (NIPE) guidance. High predictive value with low population prevalence indicates that these are cost reducing and clinically valuable markers of disease that could provide value if within a national screening program.